Importancia de la orientación diagnóstica en hemofilia A adquirida (2019)
Acquired hemophilia A (AHA) is a rare and life-threatening autoimmune hemorrhagic disorder where autoantibodies are developed against factor VIII. An early diagnosis is challenging and mandatory: an immediate hemostatic control is required to reduce morbidity and mortality. Laboratory features of AHA are: presence of autoantibodies against factor VIII, prolonged activated partial thromboplastin time (with normal prothrombin time and thrombin time) and decreased factor VIII levels. In some cases, the results of laboratory tests may be incorrect due to errors in analysis, blood extraction or manipulation of samples; also worth of consideration are limitations in the measurement range and low sensitivity of the tests. This review highlights the importance of adequate screening in patients with suspected AHA to make an adequate diagnosis and reduce overall fatal outcomes